Research of service-differentiated admission control based on Markov decision processes in heterogeneous wireless networks - DENG Qiang1; CHEN Shan-zhi2; HU Bo1; SHI Yan1 (Tongxin xuebao)
Service-differentiated admission control was studied in heterogeneous wireless networks.Capacity regions of voice and data services in CDMA cellular network and WLAN were derived.A theoretical model of admission control with differentiated services was proposed on basis of Markov decision processes theory,in which the admission actions were specified for each traffic service and system state transition probabilities were formulated.Furthermore,a fuzzy logic admission utility evaluation mechanism was presented based on the analysis of relationship of QoS requirements and network state,then the optimal admission control policy that maximizes overall utility with new and handoff call blocking probability constraints was formulated.The simulation results reveal that network dynamics can be captured by the proposed utility evaluation mechanism.And the average utility earned in the optimal admission control policy was significantly larger than two other schemes in which service differentiation and mobility are not considered,in addition,the new and handoff call blocking probability can be strictly constrained.